Peningkatkan kemampuan pendidik PAUD dalam membuat APE dengan penerapan metode tutor sebaya - Widiyantara, Widiyantara (Universitas Sebelas Maret, 2021)
This paper attempts to describe the peer tutoring method in order to improve the ability of PAUD educators in making APE. with the application of peer tutoring methods. Furthermore, it is conveyed about the steps of the peer tutor method. This step is divided into two, namely preparation and implementation. The preparatory step contains the selection of peer tutors and technical explanations for implementation. The implementation stage includes the activity process to the evaluation. The essence of learning activities with the peer tutor method here is that the activities are carried out in small groups. Each group is guided by one peer tutor. If there is more than one group in the activity, then in the following activity a shift of peer tutors will be carried out to guide other groups. this is done because in one activity, each tutor will provide different material and so on. Thus, the more often you apply the method of learning with peer tutors as mentioned above, the ability of PAUD educators in making APE will increase.Keywords: PAUD Educator, Method, Peer Tutor